Práticas pedagógicas nos Anos Iniciais do Ensino Fundamental na Abordagem Ciência-Tecnologia-Sociedade (CTS): um olhar para as pesquisas acadêmicas brasileiras - Oliveira, Mikaelly Ferraz de (2025)
The master’s degree research “Pedagogical practices in the Early Years of Elementary School in the Science-Technology-Society (CTS) approach: a look at Brazilian academic research” links to Training, Teacher Professionalization and Educational Work from Programa de Pós-Graduação em Educação da Universidade Federal de Goiás (PPGE UFG) and it aimed to explain how STS approach was historically constituted and what relations were established with pedagogical practices in Initial Years of Brazilian Elementary School? The Science-Technology-Society (STS) approach was developed during a context of criticism of developmental model that dominated part of world and got visibility in science teaching field, since the moment it substantiated the Parâmetros Curriculares Nacionais (PCNs) (Brazil, 1998). The theoretical-methodological reference substantiates itself in Marx (2017), Kopnin (1978), Kosik (1976), Lefebvre (1995) and Cheptulin (1982). To discuss scientific knowledge and teaching, Oliveira (2019) and Otto (2021) guide us, and to substantiate the STS approach, we support ourselves in the studies of Pinheiro (2005), Auler (2002), Linsingen (2007), Santos (2016), Santos and Mortimer (2000) and Strieder (2012). This research sets itself as a research ruled by historical-dialectical materialism (HDM), as a method of investigation and analysis, which bibliographic study, of the knowledge state type, selected the academic productions in Biblioteca Digital Brasileira de Teses e Dissertações (BDTD). The search of material to be analyzed should contain in title, abstract or key-words, through the following descriptors, combined: ((science AND technology AND society) OR (STS) AND (elementary school OR initial years). It was found and analyzed in six dissertations, released in the period from 2004 to 2023. In general, it is highlighted that the main STS study objects in Initial Years of Elementary School are teaching contents, mainly the contents connected to human feed and to energetic resources, and the curriculum. The analysis of researches revealed the STS conceptions linked to North American and South American strand became prominent in the analyzed corpus. Recurrence of dialectical conceptions of school knowledge in analyzed researches. However, most of researches was based on technocentric approach to discuss technology, therefore, substantiated in formal logic. We emphasize the necessity of an educational project that resists to capitalism hegemonic project and collaborates for a critic and emancipating formation of the Brazilian youth.